2007
DOI: 10.1021/ol070749f
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Catalytic Aromatic Decarboxylation Reaction

Abstract: A palladium-catalyzed aromatic decarboxylation reaction has been developed. With electron-rich aromatic acids, the reaction proceeds efficiently under fairly mild conditions in good yields. The method was useful with complex functionalized substrates containing hindered carboxylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(115 citation statements)
references
References 12 publications
4
110
0
1
Order By: Relevance
“…In order for monoortho-substituted benzoic acids 28 and less electron rich benzoic acids 29 to undergo decarboxylation a stoichiometric amount of palladium was required (Scheme 6). 26 Mechanistic studies by various groups 14 have shown a very distinct reaction profile for the palladium system compared to those for copper and silver; firstly the decarboxylation proceeds through a 4-membered transition state with no interaction with the carboxyl carbon (see 31 vs. 8 and 19, Scheme 7).…”
Section: Methodsmentioning
confidence: 99%
“…In order for monoortho-substituted benzoic acids 28 and less electron rich benzoic acids 29 to undergo decarboxylation a stoichiometric amount of palladium was required (Scheme 6). 26 Mechanistic studies by various groups 14 have shown a very distinct reaction profile for the palladium system compared to those for copper and silver; firstly the decarboxylation proceeds through a 4-membered transition state with no interaction with the carboxyl carbon (see 31 vs. 8 and 19, Scheme 7).…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Recently, Gooßen et al 6 disclosed protiodecarboxylation of arene carboxylic acids with catalytic amounts of copper/1,10-phenanthroline-complex, albeit the practical applicability of the scope was limited by it's requirement of high temperatures (160e190 C). As investigations were directed toward decreasing the high temperature required in protiodecarboxylation reactions to decrease the thermal stress during the course of the reaction and expand substrate compatibility, Kozlowski et al 7 presented palladium catalyzed protiodecarboxylation of particularly electron-rich bis-ortho-substituted aromatic carboxylic acids at much lower temperatures (<100 C) compared to other methods. 8 However this procedure requires as much as 20 mol % of the expensive Pd(O 2 CCF 3 ) 2 catalyst and 10 equiv of trifluoroacetic acid co-solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The examples demonstrate that the scope of the new Ag-catalyst is broader than that of the published Pd-system. 10 Moreover, its performance nicely complements that of the Cu-catalyst, the latter being particularly suited for meta-and para-substituted benzoic acids, while the Ag-system is highly effective for many ortho-substituted or heterocyclic derivatives that gave low or no yields with the Cu-catalyst. Examples include 2-methoxybenzoic, 2-halobenzoic, and heteroarenecarboxylic acids.…”
mentioning
confidence: 96%
“…9 The new protocol involves a copper/1,10-phenanthroline-complex as the catalyst for an effective decarboxylation of a wide spectrum of aromatic carboxylic acids within 16 h at 170 1C. Independently, Kozlowski et al 10 disclosed a catalytic protodecarboxylation protocol for particularly electron-rich bis-ortho-substituted aromatic carboxylic acids. 11 It proceeds readily at 70 1C, but involves the use of as much as 20 mol% of expensive Pd(O 2 CCF 3 ) 2 as the catalyst.…”
mentioning
confidence: 99%